Performance Audit of Rural Hospitals and Primary Health Centres in West Bengal (1999-2004) - CAG of India (CAG of India, 2005)
Healthcare is provided to rural people through a network of sub-centres, primary health centres (PHCs) and rural hospitals (RHs). There were huge shortages in numbers of RHs and PHCs as compared to the norm in West Bengal. Only 31 per cent of doctors available were working in rural areas to serve 72 per cent of the population. Specialist services were not provided in RHs. Most of the sub-centres were functioning without adequate infrastructure and health assistants (Male). Indoor treatment was not provided in most of the PHCs. Supply of medicines to RHs and PHCs was highly inadequate. In the PHCs, even routine treatment in out patient department was not provided. Main audit findings are presented below: 1. During 1999-2003, scheme fund of Rs 8.73 crore were not released by the department for development of health care services. The department also failed to utilise 52 per cent (Rs 111.52 crore) of plan funds. 2. As compared to national norms, only 20 per cent of RHs, 61 per cent of PHCs and 78 per cent of SCs were established against requirement while in the test-checked districts shortage of RHs ranged between 76 and 95 per cent and for PHCs it was between 32 and 50 per cent except in Bankura. During 1999-2004, only 10 PHCs were set up in the State. 3. Basic minimum health care services were not provided due to failure in providing requisite instruments, labour rooms, laboratory, electricity, toilet, etc. in sub-centres and PHCs. 4. In four selected districts, 27 per cent of sanctioned posts of MOs, nurses and other para medical staff remained vacant as of March 2004. Out of 236 PHCs, 177 PHCs were functioning with only one MO each against the norm of minimum two and 54 PHCs remained non-functional for one to five years for want of MOs. 5. Only 31 per cent of doctors were deployed in rural areas to serve 72 per cent of total population leading to wide disparity between urban and rural areas. Against 20712 health assistants needed for the sub-centres at village level only 14155 (68 per cent) were available. 6. Bed occupancy in test-checked 11 RHs and 12 BPHCs ranged between five and 63 per cent during 1999-2004. Low bed occupancy was noticed inall the test-checked RHs and BPHCs due to inadequate facilities, lack of doctors and non-operational Out Patient Departments. Further, out of 1013 beds in 182 PHCs of selected districts only 46 beds in five PHCs were functional. In the health centres, patients suffering from even routine ailments like fever, diarrhoea and vomiting were denied treatment in out patient department and referred to district or sub-divisional hospitals. Surgeons and anaesthetists were not deployed in fully equipped 15 OTs. 7. Equipment costing Rs 52.67 lakh was lying idle in the health centres for want of adequate infrastructure. 8. Medicines were procured without indents or assessment of requirement. In test-checked seven RHs and four BPHCs of two districts supply of medicines fell short by 24 to 47 per cent. 9. Four Zilla Parishads incurred expenditure of Rs 2.08 crore by diverting funds from the Pradhan Mantri Gramodaya Yojana. Furniture and medicines valuing Rs 14.91 lakh and Rs 34.79 lakh respectively remained unutilised due to imprudent purchases. 10. In the State, coverage of eligible couples adopting family planning measures was 33.62 per cent against the target of 60 per cent while in test-checked districts it ranged between 21 and 50 per cent. 11. During 1999-2003, out of 8.40 lakh childbirths in three test-checked districts 6.75 lakh deliveries were non-institutional and the incidence of child death increased two fold during 1999-2003.
For the Period 1999-2000 to 2003-04